The Effect of PBL Compared to Direct Instruction on Critical Thinking Skills in Fractions in Elementary School - Indri Rahmawati, Indri Rahmawati; Mardiyana, Mardiyana; Chumdari, Chumdari (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Mathematics learning in elementary schools is often still dominated by teacher-centered direct learning methods, which do not provide sufficient opportunities for students to develop critical thinking skills. However, critical thinking skills are very important in understanding mathematical concepts, including fractions. Therefore, a learning model that encourages students to actively solve problems and think deeply is needed, one of which is through the Problem-Based Learning (PBL) model. This study aims to examine the difference in critical thinking skills between students who learn using the PBL learning model and students who learn using the direct learning model in fractions. This study uses a quantitative approach with a quasi-experimental design. The research subjects consist of two groups, namely the experimental class that received learning using the PBL model and the control class that used direct learning. Critical thinking skills data were obtained through tests administered after the learning process, then analyzed using statistical techniques to determine the differences between the two groups. The results showed that there were differences in critical thinking skills between students who learned using the PBL model and students who learned using the direct learning model. The PBL learning model has a better effect on improving students' critical thinking skills in fractions. Thus, it can be concluded that the learning model affects students' critical thinking skills in mathematics learning